The Annales and the interdisciplinarity: a balance of Brazilian polemicist historiography - Suzano Junior, Barthon Favatto [UNESP] (Univ Estadual Londrina, 2019)
The interdisciplinarity was associated with the Annales (1929 - ...). In the 20th century, few historiographical movements or schools went so far and successful in the attempt to inscribe the dialogue with other disciplines as a slogan of practices and historiographic knowledges such as the magazine and the segment inaugurated by Marc Bloch and Lucien Febvre. In these pages, the comparative analysis seeks to understand how the so-called Brazilian polemicist historiography presents, understands and treat the relationship between the Annales of the first two generations and the interdisciplinarity. The approach focuses on the critical re-reading of two fundamental and far-reaching works produced and published in Brazil: Escola dos Annales: a inovacao em Historia (Paz & Terra, 2000), by Jose Carlos Reis; and Teoria da Historia: a Escola dos Annales e a Nova Historia (VOZES, 2012), volume V, which integrates the collection Teoria da Historia under the signature of the historian Jose D'Asuncion Barros. The article also seeks to problematize them from the perspective of the tension between the federalist character of History advocated by the Annales and the tradition-rupture phenomenon.
Keywords: Annales; Interdisciplinarity; Polemicist historiography; Theory; Historiographical debates